WAQF AND ZAKAT AS PHILANTHROPIC FUNDRAISING INSTRUMENTS IN HIGHER EDUCATION: EVIDENCE FROM MALAYSIAN PUBLIC RESEARCH UNIVERSITIES - M.M. Mohd Sadiq; M.I. Rohayati; H.P.S. Abdul Khalil; M.S. Shaharudin (Malaysian Journal of Learning and Instruction, 2025)
Purpose – Since 2008, government funding for higher education institutions (HEIs) has declined globally, resulting in reduced quality, higher tuition fees, and increased reliance on philanthropic contributions. This issue has been further exacerbated by the COVID-19 pandemic, prompting many PHEIs to turn to philanthropic fundraising. This study explores how Malaysian public research universities (MRUs) utilise Islamic philanthropic instruments—specifically waqf and zakat—to support student teaching and learning. It examines the successes and challenges of these initiatives and proposes a framework for optimising the use waqf and zakat as sustainable fundraising strategies in Malaysian public higher education institutions (PHEIs).